An approach for the production scheduling problem when lot streaming is enabled at the operational level - Novas, Juan M. (2018)
By means of the present work, the production scheduling and the lot streaming problems are simultaneously addressed at flexible manufacturing environments. The proposal is based on a Constraint Programming (CP) formulation that can efficiently tackle the scheduling of manufacturing operations and the splitting of lots into smaller sublots. The approach is capable to define the number of sublots for each lot and the number of parts belonging to each sublot, as well as the assignment of the operations on sublots to machines, with their corresponding start and completion times. The CP model can be easily adapted to cope with different problem issues and several operational policies, which constitutes the main novelty of the contribution. A set of case studies were solved in order to validate the proposal and good quality solutions were found when minimizing the makespan.